Change Management in Mergers and Acquisitions - Paul, Karnica (2008)
More and more firms are looking at Mergers and Acquisitions as a relatively fast and efficient way to expand into new markets and incorporate new technologies. From a strategic point of view, Mergers and Acquisitions are thought to strengthen and sustain their position in the market place. Still this strategy’s success is by no means assured. On the contrary, a majority of these Mergers & Acquisitions fall short of their confirmed goals and objectives. Some failures can be explained by financial and market factors, but many can be traced to neglected culture and human resource issues. There have been many studies done to highlight the importance of addressing the “soft” issues i.e. the people in merger and acquisition activities.